Analysis of factors associated with the presence of Aedes aegypti larvae in working area of Community Health Centre III, South Denpasar - Ida Bagus Ekaputra; Luh Seri Ani; Ketut Suastika (Universitas Udayana, 2013)
The Public Health Center (PHC) III of South Denpasar is one of the endemic areas of Dengue Hemorrhagic Fever (DHF) in Denpasar, Bali Province. Dengue morbidity rate was high (>55 per 100,000 population), while the Percentage of Larvae Free Rate (PLFR) was low (<95%). This study aims at discovering the relationship between community's knowledge, attitude, behavior of Aedes aegypti (Ae. aegypti) larvae eradication and environmental health with the existence of Ae. aegypti larvae in the working area of PHC III of South Denpasar. A cross-sectional study was conducted with 147 households using systematic random sampling from a total of 5781 households. The respondents were the head of the family unit. The independent variables were knowledge, attitude, behavior and environmental health, while the dependent variable was the presence of Ae. aegypti mosquito larvae. The data were collected by using interview and observation in the respondent's house using instruments of questionnaire. The data were then analysed in stages covering the univariate, bivariate and multivariate analysis. Results indicated the PLFR was 87.1%. The variables related to the existence of larva were behavior (PR=17.89; 95%CI: 4.99-64.11) and environmental health (PR=7,08; 95%CI: 2.48-20.23). Multivariate analysis revealed that dominant variable was the behavior (PR=11,60, 95%CI: 2,98-45,13). Meanwhile, knowledge and attitude were not statistically associated with the existence of larvae. It can be concluded that the behavioral changes efforts that support of Ae. aegypti larvae eradication is still needed. It was recommended that the PHC needs to upscale health promotion efforts addressing the severity of DHF and prevention methods, cross-sector coordination, and involvement from healthcare providers as well as specially employed field workers in developing societies to eradicate mosquito breeding in order to increase the community's behavior of mosquito-larva eradication in order to increase the PLFR and to reduce the incidence rate of DHF.